Clinical Features of the Course of Chickenpox and its Pathogenesis in the Skin (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
From January 2022 to December 2022, 201 patients aged 2 months to 52 years were treated at the Bukhara Regional Infectious Diseases Hospital, including 126 (63%) children aged 2 months to 17 years and 75 (37%) adults aged 18 to 52 years. patients, most of whom were men. Epidemiological and anamnestic anamnesis, clinical course of the disease, clinical-laboratory results were analyzed in all patients, and characteristics of the clinical course in children and older patients with chicken pox were studied.